1997
DOI: 10.1172/jci119860
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial ischemia induces differential regulation of KATP channel gene expression in rat hearts.

Abstract: The cardiac ATP-sensitive potassium (KATP) channel is thought to be a complex composed of an inward rectifier potassium channel (Kir6.1 and/or Kir6.2) subunit and the sulfonylurea receptor (SUR2). This channel is activated during myocardial ischemia and protects the heart from ischemic injury. We examined the transcriptional expression of these genes in rats with myocardial ischemia. 60 min of myocardial regional ischemia followed by 24-72 h, but not 3-6 h, of reperfusion specifically upregulated Kir6.1 mRNA n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…6,7 It has previously been reported that Kir 6.1 expression is also induced by exposure of the intact heart to I/R. 15 By exposing cultured cardiac cells to 4 hours of simulated ischemia followed by varying periods of reoxygenation, we confirmed that this effect could also be observed in culture with induction of Kir 6.1 being maximal at 16 or 24 hours of reperfusion (Figure 3a). Interestingly, we have previously shown that expression of Ucn itself is induced in cardiac myocytes exposed to ischemia 3 and is responsible for the protective effect of the conditioned medium obtained from ischemic cardiac myocytes.…”
Section: Kir 61 Is Induced By I/r But Not By Ct-1supporting
confidence: 81%
“…6,7 It has previously been reported that Kir 6.1 expression is also induced by exposure of the intact heart to I/R. 15 By exposing cultured cardiac cells to 4 hours of simulated ischemia followed by varying periods of reoxygenation, we confirmed that this effect could also be observed in culture with induction of Kir 6.1 being maximal at 16 or 24 hours of reperfusion (Figure 3a). Interestingly, we have previously shown that expression of Ucn itself is induced in cardiac myocytes exposed to ischemia 3 and is responsible for the protective effect of the conditioned medium obtained from ischemic cardiac myocytes.…”
Section: Kir 61 Is Induced By I/r But Not By Ct-1supporting
confidence: 81%
“…8,25,53 Interestingly, recent studies unrelated to KATP channels have shown that myocardial infarction, 54 myocardial reperfusion injury, 55 heart failure, 56,57 or myocyte hypertrophy 58 induce an overexpression of FoxO. Other studies unrelated to FoxO have shown increased expression of KIR6.1 following ischemia 16 and exercise. 17 Moreover, recent work suggests that FoxO and KATP channels reduce cardiac ageing and electrical instability in drosophila.…”
Section: E30 Circulation Research February 1 2008mentioning
confidence: 99%
“…14 The brain 2 and skeletal muscle 15 express both KIR6.1 and KIR6.2. The same cardiac tissue may change its subunit composition: subunit Kir6.1 is increasingly expressed in left ventricle following ischemia, 16 exercise, 17 or treatment with K ATP channel agonist. 18 Moreover, differences in subunit composition of cardiac KATP channels arise during development, aging, and between male and female.…”
mentioning
confidence: 99%
“…Kir6.1 mRNA and protein are specifically upregulated during myocardial infarction (Akao et al 1997). Mice lacking the Kir6.1 gene experience spontaneous ST elevation and atrioventricular block followed by sudden death .…”
mentioning
confidence: 99%